(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
Poverty is a multidimensional phenomenon that corresponds to certain living conditions, that is the inability to participate in the social life of the community we belong to. There have always been poor people all over the world. Several years-long measurements and qualitative analyses of poverty in the Republic of Macedonia have enabled the identification of the basic profiles of poor citizens. Based on the poverty measurement and the analysis in the Republic of Macedonia, we can discuss three profiles of poor citizens: traditionally poor, chronically poor, and newly impoverished. Based on Mill’s work, this study is focused on micro-sociological research related to poverty in the Republic of Macedonia. Accepting the indisputable fact that every social occurrence is related to the social structure one way or the other; this study analyzes the newly impoverished citizens. Special attention is given to their status and role in the Republic of Macedonia.